New Small Nuclear RNA Gene-Like Transcriptional Units as Sources of Regulatory Transcripts - Pagano, Aldo; Castelnuovo, Manuele; Tortelli, Federico; Ferrari, Roberto; Dieci, Giorgio; Cancedda, Ranieri (PLOS Genetics, 2007)
Author SummaryAfter the sequence of the human genome was determined, it was immediately recognized that a large part of the regulation of the gene expression occurring in the cells under physiological, as well as under pathological conditions, is carried out by RNA molecules that do not code for proteins (the “noncoding portion” of the genome). Here, we focus on small RNA molecules transcribed by the RNA polymerase III and identify a novel set of approximately 30 noncoding (nc) RNA genes. We propose that these RNA transcripts play a key role in regulating the expression of specific protein-coding genes transcribed by the RNA polymerase II, thus constituting an unprecedented example of cogene/gene pairs. Furthermore, we provide evidence that the RNA polymerase III, in addition to the well-known task in the constitutive synthesis of small RNAs (such as 5S rRNA and tRNAs), also plays a key role in the area of gene-expression control. A detailed investigation of the function of one of the novel ncRNA genes, called 21A, revealed that its transcript plays a role in the control of the proliferation of some tumor cells. The above findings significantly expand our understanding of the ncRNA universe and open the way to further studies aimed at the elucidation of the molecular pathways involving this novel class of regulatory RNAs.